War, trade and the state Anglo-Dutch conflict, 1652-89 - Ormrod, David 1945-; Rommelse, Gijs 1977- (The Boydell Press, 2020)
This book re-examines the history of Anglo-Dutch conflict during the seventeenth century, of which the three wars of 1652-4, 1665-7 and 1672-4 were the most obvious manifestation. Low-intensity conflict spanned a longer period. From 1618-19 hostilities in Asia between the Dutch and English East India Companies added new elements of tension beyond earlier disputes over the North Sea fisheries, merchant shipping and the cloth trade. The emerging multilateral trades of the Atlantic world added new challenges. This book integrates the European, Asian, American and African dimensions of the Anglo-Dutch Wars in an authentically global view. The role of the state receives special attention during a period in which both countries are best understood as 'fiscal-naval states'. The significance of seapower is reflected in the public history of the Anglo-Dutch wars, acknowledged in the concluding chapters. The book includes important new research findings and imaginative new thinking by leading historians of the subject